Nd and Sr Isotopes and REE Investigation in Tropical Weathering Profiles of Amazon Region - Horbe, Adriana Maria Coimbra; Albuquerque, Márcio Fernando Dos Santos; Dantas, Elton Luiz (Frontiers in Earth Science, 2022)
The exceptional development of lateritic profiles make Amazônia one of the best places to conduct a refined study on the effects of long-term tropical climate on Earth's surface rocks. To this end, Nd and Sr isotopes, as well as REE, Sr and other trace elements concentrations were determined in order to sheds new light into the behavior and the processes controlling the geochemistry and the transfer of these elements among the compartments of the critical zone. Our investigation indicated natural sotope transformations in the top of all profiles. The ƐNd(t=0) values of the parent rock, mottled horizon, lateritic duricrust are less radiogenic and similar to the Amazon craton signature and much more radiogenic and less variable in the thick oxisol where Zr, Th, Y and REE are in higher concentrations. These issue highlight a complex process for the Nd system and four possibilities are indicate to explain this behavior: formation of authigenic cerianite and kaolinite, penetration of low-temperature weathering solutions along zircon fractures, and some vegetation uptake. These possibilities allow hosts the more radiogenic Nd isotopes while the less radiogenic Nd is released especially in the oxisol. The Sr system instead of Nd, became less radiogenic along the profiles and relative to the parent rocks, as a consequence of nearly all Sr was removed in the K-Rb feldspar and mica weathering. However, mixture with less radiogenic Sr from plant returns, biogenic aerosol, and rainwater may have helped let the weathering profiles less radiogenic. These characteristics let the oxisol that is the most leached part of the profiles, even less Sr radiogenic but still allowing to identify the general parent rocks signature instead of Nd highly fractionated in the oxisol relative the parent rock. Thus, the REE and Sr behavior, similar in the six pofiles, do not necessary reflect only the parent rock geochemistry, but depends on the multiplesurficial processes typical of the critical zone: weathering, pedogenesis, plant root activity and rainwater composition.